Evaluation of formula and antibacterial activity of spray preparation from combination of aloe vera (Aloe vera L.) and lime concentrate (Citrus aurantiifolia) as hand sanitizer - Agustin, Eriska; Arsa, Arvianida Nafilah; Soyata, Amelia (Universitas Mataram, 2025)
Aloe vera plant (Aloe vera l.) has antioxidant activity and can be used as a moisturizer, especially on the inside of the leaves. Lime plant (Citrus aurantiifolia) has antibacterial activity, one of the compounds it contains is limonene. This study aims to evaluate the formula and antibacterial activity of a spray preparation combining aloe vera and lime concentrate as a Hand Sanitizer. The Hand Sanitizer spray formulation consists of four formulas with variations in the concentration of aloe vera and lime concentrate, namely F0 (0), F1 (30:20), F2 (25:25), and F3 (20:30). The evaluation carried out for 28 days includes organoleptic tests, homogeneity, pH, viscosity, drying time, and antibacterial activity. The organoleptic and homogeneity test results showed that F1, F2, and F3 were in homogeneous liquid form, cloudy orange in color, and had a distinctive lime aroma. The pH test obtained a range of 3.75-5.79. The viscosity test obtained a viscosity range of 1.06-1.29 cps. The drying time test obtained a time range of 33-46 seconds. The results of the antibacterial activity test showed that the highest inhibitory value was in formula F3 with values (14.5±0.2nm), followed by Formula F2 (11.5±0.45nm) and F1 (8.2±0.25nm). Based on statistical testing, it was concluded that there was an effect of each formula on antibacterial activity.